Filosofi Pendidikan Tauhid sebagai Fondasi Utama dalam Pendidikan di Pesantren An Nahl Sragen - Hamdani, Arfan; Hermawan, Rudi; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
This study provides an in-depth examination of the philosophy of tauhid-based education, which serves as the foundational pillar of the educational system at Pesantren An Nahl Sragen. Tauhid education is positioned as the core of all learning processes, character development, and personality formation of the students (santri). A qualitative approach was employed, with data collected through observation, in-depth interviews, and document analysis. The findings reveal that Pesantren An Nahl applies tauhid not merely as a subject of instruction, but as a comprehensive paradigm for thinking, behaving, and acting in daily life. This philosophy is integrated into the curriculum, teaching methods, and moral-spiritual development, creating an educational environment that harmoniously combines creed (akidah), ethics (akhlak), and knowledge. The study affirms that tauhid-based education plays a central role in shaping a generation that is faithful, knowledgeable, and morally upright in accordance with Islamic values.